Women and agricultural productivity: What does the evidence tell us? - Cheryl R. Doss (Yale University, Economic Growth Center, 2015)
Should agricultural development programs target women in order to increase productivity? This paper reviews the extensive literature on men's and women's relative productivity in agriculture, most of which concludes that controlling for access to inputs, plot and farmer characateristics, there are little or no gender gaps in productivity. In addition, the paper identifies the many challenges to disentangling individual level productivity. Most of the literature compares productivity on plots managed by women with those managed by men, ignoring the majority of agricultural households in which men and women are both involved in management and production. The empirical studies which have been done provide scant evidence for where the returns to project may be highest, in terms of who to target. Yet, programs that do not consider the gendered responsibilities, resources and constraints, are unlikely to succeed, either in terms of increasing productivity or benefitting men and women smallholder farmers.
Keywords: O33; O20; Q12; 330; agricultural productivity; gender; smallholder farming; developing countries; agricultural policy